Effect of exercise training on Ca2+ release units of left ventricular myocytes of spontaneously hypertensive rats - M.A. Carneiro-Júnior; J.F. Quintão-Júnior; L.R. Drummond; V.N. Lavorato; F.R. Drummond; M.A. Amadeu; E.M. Oliveira; L.B. Felix; J.S. Cruz; J.G. Mill; A.J. Natali; T.N. Prímola-Gomes (Brazilian Journal of Medical and Biological Research, 2014)
In cardiomyocytes, calcium (Ca2+) release units comprise clusters of intracellular Ca2+ release channels located on the sarcoplasmic reticulum, and hypertension is well established as a cause of defects in calcium release unit function. Our objective was to determine whether endurance exercise training could attenuate the deleterious effects of hypertension on calcium release unit components and Ca2+ sparks in left ventricular myocytes of spontaneously hypertensive rats. Male Wistar and spontaneously hypertensive rats (4 months of age) were divided into 4 groups: normotensive (NC) and hypertensive control (HC), and normotensive (NT) and hypertensive trained (HT) animals (7 rats per group). NC and HC rats were submitted to a low-intensity treadmill running protocol (5 days/week, 1 h/day, 0% grade, and 50-60% of maximal running speed) for 8 weeks. Gene expression of the ryanodine receptor type 2 (RyR2) and FK506 binding protein (FKBP12.6) increased (270%) and decreased (88%), respectively, in HC compared to NC rats. Endurance exercise training reversed these changes by reducing RyR2 (230%) and normalizing FKBP12.6 gene expression (112%). Hypertension also increased the frequency of Ca2+ sparks (HC=7.61±0.26 vs NC=4.79±0.19 per 100 µm/s) and decreased its amplitude (HC=0.260±0.08 vs NC=0.324±0.10 ΔF/F0), full width at half-maximum amplitude (HC=1.05±0.08 vs NC=1.26±0.01 µm), total duration (HC=11.51±0.12 vs NC=14.97±0.24 ms), time to peak (HC=4.84±0.06 vs NC=6.31±0.14 ms), and time constant of decay (HC=8.68±0.12 vs NC=10.21±0.22 ms). These changes were partially reversed in HT rats (frequency of Ca2+ sparks=6.26±0.19 µm/s, amplitude=0.282±0.10 ΔF/F0, full width at half-maximum amplitude=1.14±0.01 µm, total duration=13.34±0.17 ms, time to peak=5.43±0.08 ms, and time constant of decay=9.43±0.15 ms). Endurance exercise training attenuated the deleterious effects of hypertension on calcium release units of left ventricular myocytes.